The autonomous system : a foundational synthesis of the sciences of the mind - De Gyurky, Szabolcs Michael (Wiley, 2014)
"This book describes--in modern computer science terms--the Level II architecture of the meaning and definition of the process referred to as "thinking." It applies the basis of early cognitive science research to the creation of autonomous system architectures--connecting philosophical findings of the past with cutting-edge progress in artificial intelligence. Providing an in-depth introduction to the classical, philosophical theories of cognitive scientists like Immanuel Kant, Arthur Schopenhauer, and G.W.F. Hegel, the book examines the Will System, Reason System, Imagination System, and the Communication System"--